Work-family life courses and markers of stress and inflammation in mid-life: evidence from the National Child Development Study. (14th October 2015) - Lacey, Rebecca E; Sacker, Amanda; Kumari, Meena; Worts, Diana; McDonough, Peggy; Booker, Cara; McMunn, Anne
Abstract: Background: This study investigated associations between work-family life courses and biomarkers of inflammation and stress in mid-life among British men and women. Gender differences in these associations were also explored. Methods: A novel statistical method—multi-channel sequence analysis—defined work-family life courses between the ages of 16 and 42 years, combining annual information on work, partnership and parenthood. Associations between work-family life courses and inflammation [C-reactive protein (CRP), fibrinogen and von Willebrand factor] and cortisol at age 44/45 years were tested using multivariate linear regression using multiply-imputed data on almost 6500 participants from the National Child Development Study 1958 British birth cohort. Results: Compared with those who combined strong ties to paid work with later transitions to stable family lives ('Work, later family' group), 'Teen parents' had higher CRP [40.6% higher, 95% confidence interval (CI): 5.6, 87.0] and fibrinogen (7.8% higher, 95% CI: 2.3, 13.5) levels, and homemakers ('No paid work, early family') had raised fibrinogen levels (4.7% higher, 95% CI: 0.7, 9.0), independent of childhood health and socioeconomic position, adult socioeconomic position, health behaviours and body mass index (BMI). Those who combined later transitions to stable family ties with a career break for childrearing had higher post-waking cortisol than the 'Work, later family' group; however, no associations were seen for other work-family types, therefore suggesting a null finding with cortisol. No statistically significant gender interactions in associations between work-family types and inflammatory or cortisol outcomes were found. Conclusions: Work-family life courses characterised by early parenthood or weak work ties were associated with a raised risk profile in relation to chronic inflammation.